Characteristics of Nontyphoid Salmonella Isolated from Human, Environmental, Animal, and Food Samples in Burkina Faso: A Systematic Review and Meta-Analysis - Kuan Abdoulaye Traore; Abdoul Rachid Aboubacar-Paraiso; Soutongnooma Caroline Bouda; Jean Bienvenue Ouoba; Assèta Kagambèga; Pierre Roques; Nicolas Barro (MDPI AG, 2024)
Salmonella is one of the world's leading causes of zoonotic and foodborne illnesses. Recently, antimicrobial resistance (AMR) has become one of the most critical challenges to public health and food safety. Herein, we employed a meta-analysis to determine the pooled prevalence and spatiotemporal distribution of serovars and antimicrobial resistance in NTS in Burkina Faso. To find eligible articles, a comprehensive literature search of PubMed, African Journals Online, ScienceDirect, Google Scholar, and the gray literature (university libraries) in Burkina was conducted for the period from 2008 to 2020. Studies meeting the inclusion criteria were selected and assessed for risk of bias. To assess the temporal and spatial relationships between serotypes and resistant strains from humans, animals, food, and the environment, a random-effects statistical model meta-analysis was carried out using the Comprehensive Meta-Analysis Version 3.0 program. The NTS prevalence rates were 4.6% (95% CI: 3-7) and 20.1% (95% CI: 6.6-47.4) in humans and animals, respectively, and 16.8% (95% CI: 10.5-25.8) and 15.6% (95% CI: 8.2-27.5) in food and the environment, respectively. Most NTS serovars were S. Derby, reported both in food and animals, and S. Typhimurium, reported in humans, while S. Croft II, S. Jodpur II, and S. Kentucky were the most prevalent in the environment. NTS isolates were highly resistant to erythromycin, amoxicillin, cefixime, and cephalothin, with a pooled prevalence of multidrug resistance of 29% (95% CI: 14.5-49.5). The results of this review show a high diversity of Salmonella serotypes, as well as high antibiotic resistance in Salmonella isolates from animal, human, food, and environmental samples in Burkina, calling for a consolidated "One Health" approach to better understand the drivers of pathogen emergence, spread, and antimicrobial resistance, as well as the formulation of intervention measures needed to limit the risk associated with the disease.